Profile of Computational Thinking Skills in Environmental Chemistry Courses for Prospective Science Teacher Students - Emilia Candrawati; Mellyta Uliyandari; Nuryani Y. Rustaman; Ida Kaniawati (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
Computational thinking skills are not only provided to students in computer-related courses, but also in all courses, including Environmental Chemistry courses. Environmental chemistry courses are considered important because they orient students to the achievement of scientific literacy and awareness. Therefore, optimization of learning in environmental chemistry courses also needs to be carried out to support the achievement of CPL which includes 21st-century life skills, including computational thinking skills. science teacher candidates. The research method follows 3 stages of field study, namely preparation, data collection, and data analysis. The results of the study show that the Science Education Study Program has poured CT skills into CPL, environmental chemistry lectures are still dominated by theoretical explanations by lecturers, lecturers do not understand the concept of CT, and CT skills are very important to provide students.